Fostering SME supplier‐enabled innovation in the supply chain: The role of innovation policy. Issue 1 (28th September 2021) - Selviaridis, Kostas; Spring, Martin
Abstract: Buying organizations collaborate with their suppliers to innovate, and increasingly seek to tap into the innovation potential of technologically adept small and medium‐sized enterprises (SMEs) who are new to them. Engagement with technology‐based SMEs as possible suppliers can be constrained by institutions (e.g., rules, regulations, and norms of conduct) embodied in the buying organization's procurement and supply chain strategy, processes, and practices. Although prior research has examined how institutional forces influence supplier‐enabled innovation, little is known about institutional failures that are particularly germane to innovative SMEs and impede collaboration between these SMEs and buying organizations. Consistent with the focus of the second emerging discourse incubator (EDI) on researching the effects of institutions (e.g., regulations) and public policies on supply chains, we investigate how enacted innovation policies address SME‐specific institutional failures in a public sector context, that of the English National Health Service (NHS). Our qualitative research reveals that public agencies responsible for policy enactment seek to promote SME supplier‐enabled innovation in the supply chain through institutional change and mitigation, SME connectivity to supply chain actors, and SME supplier development support. We synthesize our findings into a research model and set of propositions which theorize on the specific mechanisms underpinning the interventions of policy‐enacting agencies and their effects. Our study contributes to the literature on supplier‐enabled innovation and to research focusing on collaboration between buyers and innovative small suppliers. More broadly, we generate theoretical insights regarding the role of public agencies enacting policy as a class of non‐firm actors whose interventions influence the supply chain. The findings also add to our understanding of the interplay between supply chains and institutions.